Noise Sources and Levels in Intensive Care Units - Emine Kol; Emine İlaslan; Serpil İnce (Galenos Yayinevi, 2015)
Objective: Noise has been an important problem for both patients and healthcare workers at hospitals. The study was aimed at determining noise sources and noise levels intensive care units. Material and Method: Noise level measurements were performed in four weeks between March 01, 2012 and April 01, 2012. Noise measurement was performed using a Extech 407780 sound level meter during 24 hours. At the same time, observation was performed to identify the sound sources and the highest noise sources were noted by researcher. The sound level meter was placed on the wall between two patient beds and the nurses' station. Results: The sources of the highest noises were the conversation voices coming from the nurses' station (84.1 dB(A)) and perfusor alarm (83.2 dB(A)). Other sources of noise were the alarm sounds from the pulse oximetry (81.1 dB(A)), nebulizator (80.1 dB(A)), monitor (78.6 dB(A)), ringing phones (77.4 dB(A)), infusion pump (76 dB(A)) and ventilator (75 dB(A)). Conclusion: Staff conversations, caring activities and monitor alarm management are controlled by health Professionals. Therefore, it is particularly important in informing nurses about noise control.